Clinical Characteristics of Pediatric with Germ Cell Tumor: Experience in a Developing Country - Lelani Reniarti; Anisah Febri; Nur Melani Sari (Althea Medical Journal, 2021)
Background: Germ cell tumor (GCT) occurs in 3% of pregnancy malignancies and increases by 15% during adolescence. In developing countries, the five-year survival rate is 98% and 80% for GCT earlier stage and malignant tumor, respectively. This study aimed to gather information about clinical manifestations of GCT and to evaluate the treatment outcome in pediatric GCT patients at Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaMethods: A descriptive cross-sectional study design with a total sampling method was conducted using secondary data from the medical record of pediatric patients diagnosed with GCT from 2015 to 2018. Data on nutritional status, clinical characteristics, histopathology stage, hematological profiles, chemical markers, treatment methods, completeness of treatment, and outcome at the end of treatment were collected and presented using tables and charts.Results: Of the 44 subjects, girls (77.3%) were predominant, with a mean age of 2 years old and normal nutritional status (59.1%). Patients generally had abdominal mass (97.7%) and most had intragonadal GCT (95.5%), with ovarium (76.2%) as the most common location. The most frequent GCT histopathology was yolk sac tumor (34.1%), with an Alpha-fetoprotein (AFP) level of >100.000 (6.8%). Almost all patients (97.7%) had undergone surgery; however, 47% of patients did not complete their treatment. At the end of treatment, the majority of patients survived (86.4%).Conclusion: Germ cell tumor has various clinical characteristics. Understanding these characteristics will enable clinicians to make a proper diagnosis and provide immediate management that will lead to a better prognosis.